2020
DOI: 10.1038/s41467-020-15774-z
|View full text |Cite|
|
Sign up to set email alerts
|

Intramolecular chaperone-mediated secretion of an Rhs effector toxin by a type VI secretion system

Abstract: Bacterial Rhs proteins containing toxic domains are often secreted by type VI secretion systems (T6SSs) through unclear mechanisms. Here, we show that the T6SS Rhs-family effector TseI of Aeromonas dhakensis is subject to self-cleavage at both the N-and the Cterminus, releasing the middle Rhs core and two VgrG-interacting domains (which we name VIRN and VIRC). VIRC is an endonuclease, and the immunity protein TsiI protects against VIRC toxicity through direct interaction. Proteolytic release of VIRC and VIRN i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(125 citation statements)
references
References 69 publications
12
113
0
Order By: Relevance
“…While previous work has relied on genetic context to identify the cognate effector of an Eag chaperone ( Whitney et al, 2015 ; Alcoforado Diniz and Coulthurst, 2015 ), our use of the prePAAR motif as an effector discovery tool enables the identification of these effectors in any genetic context. Other families of chaperones, such as the DUF4123 or DUF2169 protein families, have also been shown to affect the stability and/or export of their cognate effectors ( Burkinshaw et al, 2018 ; Bondage et al, 2016 ; Pei et al, 2020 ). However, little is known about the specificity of these chaperones for their effector targets, which do not contain predicted N-terminal TMDs.…”
Section: Discussionmentioning
confidence: 99%
“…While previous work has relied on genetic context to identify the cognate effector of an Eag chaperone ( Whitney et al, 2015 ; Alcoforado Diniz and Coulthurst, 2015 ), our use of the prePAAR motif as an effector discovery tool enables the identification of these effectors in any genetic context. Other families of chaperones, such as the DUF4123 or DUF2169 protein families, have also been shown to affect the stability and/or export of their cognate effectors ( Burkinshaw et al, 2018 ; Bondage et al, 2016 ; Pei et al, 2020 ). However, little is known about the specificity of these chaperones for their effector targets, which do not contain predicted N-terminal TMDs.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the T6SS DNase effector (Tde) toxins belong to the HNH superfamily, also known as His‐Me finger endonucleases (Alcoforado Diniz & Coulthurst, 2015; Koskiniemi et al, 2013; Pei et al, 2020; Pissaridou et al, 2018; Zhang et al, 2012). A His‐Me finger is a short 30‐amino acid motif formed by a β‐hairpin followed by an α‐helix (ββα) that constitute a binding site for a divalent metal ion (Jablonska et al, 2017).…”
Section: Activity Of T6ss Delivered Effectorsmentioning
confidence: 99%
“…Besides DsbA, involvement of the ClpAP protease in T6SS susceptibility (Lin et al, 2020) also suggested that various types of proteases may be used for activating toxin activity by either cleaving full-length toxin proteins into more active truncated forms or degrading proteins that may inhibit toxin activity. A recent report showed that self-cleavage at both the N-and C-termini of an Rhs-family T6SS toxin TseI is not required for secretion but critical for its toxin activity (Pei et al, 2020). This finding also suggests that protease cleavage could be a strategy used for toxin activation in the recipient cell.…”
Section: Identification Via Activating Toxin Activitymentioning
confidence: 99%